Delta- and zeta-COP, two coatomer subunits homologous to clathrin-associated proteins, are involved in ER retrieval. - Cosson, P (1996)
Two new thermosensitive yeast mutants defective in retrieval of dilysine-tagged proteins from the Golgi back to the endoplasmic reticulum (ER) were characterized. While both ret2-1 and ret3-1 were defective for ER retrieval, only ret2-1 exhibited a defect in forward ER-to-Golgi transport at the non-permissive temperature. Coatomer (COPI) from both mutants could efficiently bind dilysine motifs in vitro. The corresponding RET2 and RET3 genes were cloned by complementation and found of encode the delta and zeta subunits of coatomer respectively. Both proteins show significant homology to clathrin adaptor subunits. These results emphasize the role of coatomer in retrieval of dilysine-tagged proteins back to the ER, and the similarity between clathrin and coatomer coats.